Design Design Thinking in Practice: Case Studies on Value Proposition Development - Tara Diva Azura; Astri Ghina (Innovation Business Management and Accounting Journal, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia significantly contribute to the national economy, accounting for 61.9% of the gross domestic product and employing 97% of the workforce. Even though these businesses like Kedai Wayang Windu are important, turnover for many MSMEs decreased over the pandemic. The study applies a design thinking process (empathy, define, ideate, prototype, and test) to gain deeper insight into user needs and create an offering that resonates with them. The findings focused on the customer needs, preferences, and behavior, derived via five face-to-face in-depth interviews and observation sessions of existing customers. The results show that customers encountered problems, including limited menu/price information, long waiting times, and less-than-great services. Kedai Wawind E-Menu is an idea brought in through the design thinking process. Customers can check offers and menu items and seamlessly order using this digital menu to boost speed and get faster service, focusing on enabling people to do it immediately.